Strategic Planning, External Environment and Performance of County Governments in Kenya - David, Catherine N.; Okeyo, Washington (Archives of Business Research, 2018)
The purpose of the study was to determine the effect of effect of strategic planning on organizational performance of Nairobi County. Descriptive research design was adopted in this study which targeted a total of 246 employees of Nairobi County government of whom 23 were top level managers, 61 middle level managers and 162 low level managers. Data was collected using structured questionnaire administered through drop and pick from a sample of 80 employees who were selected using stratified and sequential random sampling methods. Correlation and linear regression analysis were used to analyze the data. Regression results revealed that there was a positive and significant relationship between strategic planning and performance of the county government. Regression results further revealed that external environment has a positive and significant effect on performance of county government. In addition, external environment moderate the relationship between strategic planning and performance of county government. The study recommends that strategic formulation should be a top priority activity at every county government. County government should also employ top-bottom communication during the strategic plan implementation process. In addition, the county government should ensure they have enough competent staff to implement strategic initiatives. Adequate financial resources should also be allocated towards strategy control in their county. Performance indicators and targets should also be clearly defined and communicated within the county. In addition, employees of the county should comply with the county by laws. The county government should therefore do proper environmental scanning so as to improve their performance. The county government should also comply with the parliamentary Acts formulated from the Kenya’s 2010 constitution.